Detection of mislabeled germplasm in cocoa collections using DNA fingerprinting with SSR markers - Zhang, D.; Boccara, Michel; Mischke, S.; Motilal, L.; Kolesnikova-Allen, M.; Cryer, N.; Turnbull, C.; Lanaud, C.; Philips-Mora, W.; Butler, D. (2006)
Incorrect labeling of cocoa accessions is a significant that has hindered the efficient conservation and use of cocoa germplasm. The United States Department of Agriculture (USDA), together with the international collaborating institutions, has undertaken a program to identify the cocoa genotypes and describe the genetic diversity in the major international and national cocoa collections maintained in the Americas. To date, a total of 4027 coca accessions maintained in the two international genebanks (ICG, T and CATIE), and in several other national collections in latin America, have been genotyped with a set of 15 standard microsatalite (SSR) loci.